Federalism as a Solution to the Minority Problem - Findi , Hakar A. (Mitanni Journal of Humanitarian Sciences, 2022)
Because we are in a region full of multiple societies in terms of nationalism, religion, language, gender and other characteristics, this has imposed the presence of minorities in most countries of the region.With these differences in addition to the democratic awareness that did not exist in the past, many problems were generated, including the denial of their legitimate rights to minorities, and after they began to demand their rights, they were rejected and their demands were not recognized. Therefore, I found it necessary to go into this subject and determine the most appropriate system or mechanism to guarantee the rights of minorities, where we try in our research to reach the goals and due to the multiplicity of systems of government, and after clarifying those systems that are interested in this matter, we decided to look for a solution to the problems of minorities through the application of the federal system.